Granitoids and their Associated Mineralisation from Western Stewart Island - R Peden (The Australasian Institute of Mining and Metallurgy, 1987)
Recent, detailed mapping, (Allibone, 1986; Peden, in prep.) of north west Stewart Island, has shown that the Rakeahua Granite (Watters et al, 1968), is comprised of a wide range of granitoid bodies ranging from diorite to leucogranite. As a result of the wide variation in granitoids Allibone (1986), suggests renaming of the Rakeahua Granite to the Rakeahua Granitoid Complex. Names were also proposed for the individual granitoid bodies mapped.